1987
DOI: 10.1111/j.1365-2125.1987.tb03013.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a pharmacokinetic interaction between enalapril and frusemide.

Abstract: Single doses of enalapril maleate 10 mg and frusemide 80 mg do not significantly affect the pharmacokinetics of each other when taken concomitantly. Their concomitant use may be associated with more adverse effects than with the individual entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Following single oral doses of enalapril lOmg and frusemide 80mg, the kinetics of the 2 drugs and their metabolites did not significantly affect each other (van Hecken et al 1987). The blood pressures of the 12 healthy subjects studied were not significantly reduced by frusemide alone, but they were decreased by enalapril alone and by coadministration of enalapril plus frusemide.…”
Section: Diureticsmentioning
confidence: 83%
“…Following single oral doses of enalapril lOmg and frusemide 80mg, the kinetics of the 2 drugs and their metabolites did not significantly affect each other (van Hecken et al 1987). The blood pressures of the 12 healthy subjects studied were not significantly reduced by frusemide alone, but they were decreased by enalapril alone and by coadministration of enalapril plus frusemide.…”
Section: Diureticsmentioning
confidence: 83%
“…For example, the IC 50 of the high-affinity OAT3 substrate furosemide is 7.3 µM [ 26 ] and observed therapeutic plasma concentrations are around 3.6 µM (total concentration) [ 27 ]. After co-administration of furosemide with enalapril at therapeutic dosages of both drugs (enalapril 10 mg and furosemide 80 mg), only a non-significant increase in both the enalaprilat C max (increase from 34.9 to 38.2 ng/mL) and area under the curve (AUC) (increase from 369 to 384 ng/mL/h) were observed [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy volunteers, it has been reported that single doses of enalapril 10mg and furosemide 80mg may not significantly affect the pharmacokinetics of each other when taken concomitantly (Van Hecken et al 1987). In their study, each of 12 volunteers received at 3 occasions, separated by a 2-week washout period, a single morning dose of either enalapril 10mg, furosemide 80mg, or both.…”
Section: Thiazide and Loop Diureticsmentioning
confidence: 96%